Exploring the Experience of Informatics Education Students in Sharpening Thinking Skills Through Scratch - Tena, Beatrix Dasilva; Sogen, Maria Magdalena Beatrice; Miru, Yosep Gayus; Jaiman, Fridolin; Mowata, Seregius Erdin (JUPE : Jurnal Pendidikan Mandala, 2025)
The rapid development of information technogy necessitates that informatics Education students prosess optimal sritical, creative, and problem-solving abilities development of higher-order thinking skill. This research aims to explore student’s experinces in honing their thinking abilities through the use of Scratch as a learnig medium. The method employed is descriptive, qualitative, with data collected via quastionnaires distributed to sixth-semester students. The research findings incate that integrating Scratch encourages sdudents to be more active, and collaborative in learning, and enhances their critical, creative, and computational thinking skills. Scratch also effectively facilitates students in understanding programming logic, desgining algotithms, and solving problems independently. These findings support the winder utulization of Scratch to foster the development of thinking skills among informatics Education students.